IoT-Based Smart Water Quality Monitoring System for Early Detection of Water Pollution in Batam City - Candra, Joni Eka; Hazimah , Hazimah (Journal of Computer Networks, Architecture and High Performance Computing, 2025)
Water pollution poses a significant threat to public health, particularly in rapidly developing urban areas such as Batam City, where domestic and industrial activities continue to increase. This study aims to analyse and monitor the quality of household tap water in Batam City over a 30-day period using an Internet of Things (IoT)-based smart water quality monitoring system. The research focuses on two key parameters, namely Total Dissolved Solids (TDS) and water temperature, which serve as primary indicators of water purity. Data were collected daily through a TDS sensor and a DS18B20 digital temperature sensor integrated into an IoT platform for continuous monitoring and real-time data acquisition. The results revealed that the water temperature ranged between 28–29 °C, indicating normal conditions for tropical regions and conforming to clean water standards. The TDS values varied from 310 to 355 ppm, remaining below the World Health Organization (WHO) safety limit of 500 ppm. Although slight fluctuations in TDS levels were observed during the observation period, no readings exceeded the acceptable threshold. These findings suggest that household tap water in Batam City is still safe for consumption and daily use. The study concludes that the application of IoT-based monitoring systems offers an effective approach for real-time water quality supervision and recommends regular monitoring along with the use of filtration devices to ensure long-term water safety and sustainability